Glomerulogenesis and Histomorphometeric in Mus musculus Embryo - Alzubaidi, Amar; Al-Bakri , Nahla A.; Ateeq M. J. Alarami (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In mammals, the kidneys originate in an embryo from the mesoderm through three excretory organs, namely: Pronephros, Mesonephros, and Metanephros. After the formation of Metanephros is completed, the kidneys begin to form nephrogenesis through mesenchymal cells located at the tip of the ureteric bud, that contribute in the formation of glomerulus and Renal tubules. The stages of glomerulus formation in the embryo of albino mice at the age of 14 to 19 days of gestation were studied. It was obtained after the sacrifice of the expectant mother and the kidneys were excised from the embryos and fixed using Aqueous Bouin's solution, Microscopic slices with a thickness of 6 microns were then made in a paraffin method and were photographed by a camera for microscopic imaging. Histological measurements were performed on them using the program IMAGE J program and analyzed statistically using the SPSS program. Results of the current study showed the presence of five stages of glomerulus formation, namely, the renal vesicle, which represents the first stage in the formation of the nephron and glomerulus. This is followed by the Comma shape stage, S-shaped stage, Capillary loop stage and finally the Mature glomerulus. This is surrounded by a capsule, known as Bowman’s capsule being part of the Malpighian or Renal corpuscle. The statistical analysis showed that there were significant differences between the average diameters of the glomerular development stages, and that the mature glomerulus was larger in diameter than the rest of the stages. The study aims to determine the stages of glomerulus formation and histologically measure its diameter in the embryo of a Mus musculus.